Phase formation polycrystalline vanadium oxide via thermal annealing process under controlled nitrogen pressure - S Jessadaluk; N Khemasiri; S Rahong; A Rangkasikorn; N Kayunkid; S Wirunchit; M Horprathum; C Chananonnawathron; A Klamchuen; J Nukeaw (My University, 2017)
This article provides an approach to improve and control crystal phases of the sputtering vanadium oxide (VxOy) thin films by post-thermal annealing process. Usually, as-deposited VxOy thin films at room temperature are amorphous phase: post-thermal annealing processes (400 °C, 2 hrs) under the various nitrogen (N2) pressures are applied to improve and control the crystal phase of VxOy thin films. The crystallinity of VxOy thin films changes from amorphous to α-V2O5 phase or V9O17 polycrystalline, which depend on the pressure of N2 carrier during annealing process. Moreover, the electrical resistivity of the VxOy thin films decrease from 105 Ω cm (amorphous) to 6×10-1 Ω cm (V9O17). Base on the results, our study show a simply method to improve and control phase formation of VxOy thin films.
Keywords: Vanadium Oxide; Transition Metal Oxide Nanomaterials